Effects of the air ducts layout in the back wall on the heat transfer and storage characteristics of active heat storage back wall of solar greenhouse - Sun, Yachen; Wu, Cuinan; Zhu, Chenmeng; Li, Guoliang; Cao, Yanfei; Zou, Zhirong; Bao, Encai (International Journal of Agricultural and Biological Engineering, 2025)
Solar greenhouses have been widely developed in China. Active heat storage walls using air ducts arranged in the walls can improve the walls' thermal performance and indoor temperatures of solar greenhouses. In the present work, three kinds of air duct layouts, namely straight-up-and-down duct (Z), fork-shaped top-in- bottom-out distribution duct (DF), and “±”shaped top-in-side-out distribution duct (CF) are designed. The effect of the three air duct layouts on the heat transfer and storage characteristics of the back wall is studied using the computational fluid dynamics (CFD) method. Results show that after the same time period, the transferred heat amount in the back wall with duct DF is the largest, while that with duct CF is slightly greater than that with duct Z. The temperature of the back walls with air ducts is higher than that without air ducts. The air duct DF is the optimal among the three kinds of air duct layouts. The greenhouse with the duct DF in the back wall shows the most obviously increased indoor average temperature, the highest temperature at night, and the most uniform temperature. Keywords: active heat storage, heat transfer, air duct layout, solar greenhouse, CFD DOI: 10.25165/j.ijabe.20251804.7785 Citation: Sun Y C, Wu C N, Zhu C M, Li G L, Cao Y F, Zou Z R, et al. Effects of the air ducts layout in the back wall on the heat transfer and storage characteristics of active heat storage back wall of solar greenhouse. Int J Agric & Biol Eng, 2025; 18(4): 63–70.